IMPLEMENTASI BAHAN AJAR DIGITAL KEWIRAUSAHAAN YANG DISERTAI NILAI-NILAI ISLAM PADA MATA KULIAH KEWIRAUSAHAAN - Bahtiar Afwan; Ira Vahlia; Sangidatus Sholiha (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
Entrepreneurship learning is still a subject that is considered difficult for students because it is considered incompatible between theory and practice. Ease of access to information technology in the era of the industrial revolution 4.0 is considered to be one of the hopes in achieving learning success, especially in entrepreneurship courses. The purpose of this study is to describe the implementation of digital entrepreneurship teaching materials accompanied by Islamic values in entrepreneurship courses. This research involved 31 students taking entrepreneurship courses at one of the universities in Indonesia. The method used in this study is descriptive quantitative using percentages. The instrument used was a survey questionnaire in the form of a Google form which was distributed to students 5 times in 10 meetings. The results show that digital entrepreneurship teaching materials are interesting and help students understand the material. Students' difficulties were seen at the beginning of the meeting in using digital entrepreneurship teaching materials, but over time students began to get used to and easily use digital teaching materials. The implementation of digital entrepreneurship teaching materials accompanied by Islamic values in lectures has proven to support interactions between lecturers and students and is able to improve the independent learning process for students so that they become more effective and efficient. Keywords : digital entrepreneurship teaching materials; implementation; Islamic values